Optimalisasi Media Digital Interaktif Wordwall dalam PJJ BIPA di Kedutaan Besar Republik Indonesia di Bern, Swiss - Hilda Septriani; Yuyus Rustandi (Ranah: Jurnal Kajian Bahasa, 2023)
The development of Indonesian for Foreign Speakers (BIPA) as a soft diplomacy effort continues to increase rapidly. Various universities abroad and BIPA organizing institutions strive to open BIPA classes every semester. Every mode of learning certainly needs to be circumvented so as not to cause boredom to learners, one of which is by utilizing the available interactive digital learning media, namely Wordwall. This paper aims to identify the process of developing and optimizing the use of Wordwall in the BIPA class as an effective supporting media. In addition, it also seeks to measure the effectiveness of using Wordwall in the learning process in the classroom. The research methods used in this study were the distribution of questionnaires to learners, interview techniques, and documentation studies. The respondents in the study were students in BIPA 2 and BIPA 3 classes at the Indonesian Embassy in Bern, Switzerland in the spring semester period, which is between March–July 2022. The results showed that the development process and effectiveness of using Wordwall in learning in BIPA 2 and BIPA 3 classes could be achieved optimally which was identified through obtaining the scores of the majority of learners and the conformity of their answers during interviews. The implication of this research is that the use of digital-based teaching media, namely Wordwall in BIPA classes, also supports the success of learning objectives and becomes a new breakthrough in BIPA teaching. AbstrakPerkembangan Bahasa Indonesia bagi Penutur Asing (BIPA) sebagai upaya diplomasi lunak terus meningkat pesat. Berbagai universitas di luar negeri dan lembaga penyelenggara BIPA berupaya untuk membuka kelas-kelas BIPA setiap semester. Setiap moda pembelajaran tentunya perlu disiasati agar tidak menimbulkan kebosanan pada pemelajar, salah satunya dengan memanfaatkan media pembelajaran digital interaktif yang tersedia yaitu Wordwall. Tulisan ini bertujuan untuk mengidentifikasi proses pengembangan dan optimalisasi penggunaan Wordwall di kelas BIPA sebagai media penunjang yang efektif. Selain itu juga berupaya untuk mengukur efektivitas pemanfaatan Wordwall dalam proses pembelajaran di kelas. Metode penelitian yang digunakan dalam penelitian ini adalah penyebaran kuesioner kepada pemelajar, teknik wawancara, dan studi dokumentasi. Responden dalam penelitian adalah pemelajar di kelas BIPA 2 dan BIPA 3 di KBRI Bern, Swiss pada periode spring semester yaitu antara bulan Maret – Juni 2022. Hasil penelitian menunjukkan bahwa proses pengembangan dan efektivitas penggunaan Wordwall dalam pembelajaran di kelas BIPA 2 dan BIPA 3 dapat tercapai secara optimal yang diidentifikasi melalui perolehan skor mayoritas pemelajar dan konformitas jawaban mereka saat wawancara. Adapun implikasi dari penelitian ini adalah penggunaan media ajar berbasis digital yaitu Wordwall di kelas BIPA turut menunjang keberhasilan tujuan pembelajaran dan menjadi terobosan baru dalam pengajaran BIPA.